Attenuation Characteristics of Vibration in a Locally Resonant Phononic Crystal Frame Structure - WANG, Yukun; QIAN, Denghui; WU, Jinghong; HE, Feiyang (Archives of Acoustics, 2020)
In this paper, a frame structure based on the locally resonant (LR) mechanism of phononic crystals (PCs) is designed on account of the wide application of frame structures in high-rise buildings, and the band structures, displacement fields of eigenmodes, and transmission power spectrums of corresponding finite structure are calculated by finite element (FE) method. Numerical results and further analysis demonstrate that a full band gap with low starting frequency can be opened by the frame structure formed by periodically combining soft and hard materials, and the starting frequency can be further lowered with the adjustment of corresponding geometric parameters, which provides a theoretical basis for the studies on vibration insulation and noise reduction of high-rise buildings.